Teachers as Makers: The Key Provision of Teacher Preparations for STEM Education - Suthida Chamrat (2020)
© Published under licence by IOP Publishing Ltd. This study explores how learning activities based on maker concepts prepared pre-service teachers entering the STEM Education pipeline. 25 pre-service science teachers from the faculty of education at Chiang Mai University enrolled in an Independent Study in Science Teaching course. The course was called "Integrating maker concepts and STEM Education." The course sought to integrate existing science objectives with maker concepts and activities. Pre-service teachers were divided into 8 groups. Each group had to write and present a proposal, develop their instruments/Makings, try it out in schools, submit full reports, present and review peers' final reports, attend a regional STEM festival where they participated in poster presentations. Using the collected data from a shared Google Drive, Video recordings, interviews, and extended activities, the findings indicated that STEM concepts and practices could be conveyed to pre-service teachers by instilling the maker mindset. From the 8 groups, 3 themes emerged: research in science education, science project, and STEM Education which consisted of 1, 1 and 6 projects, respectively. The creation of artefacts or Makings required scientific and mathematical concepts, empirical testing, and technological design. These enabled pre-service teachers to understand and practice teaching and learning in the STEM field. Event case study was employed as research methodology. Details of 8 pre-service teacher projects and 5 assertions of research findings are described.